IMPLIKATUR PERCAKAPAN ANTARA PENJUAL DAN PEMBELI DI PASAR SENTRAL KABUPATEN TAKALAR - Latif, Nurwahyuni; Asia; Hajrah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe conversational implicatures between sellers and buyers at the Central Market of Takalar Regency based on violations of Grice's cooperative principle maxims. This research employed a descriptive qualitative approach. The data consisted of utterances in buying and selling interactions collected through observation, recording, and note-taking techniques. The data were analyzed based on Grice's four conversational maxims: quantity, quality, relevance, and manner. The results showed that, out of 178 utterances analyzed, 30 utterances contained maxim violations, consisting of 14 violations of the maxim of quantity, 8 violations of the maxim of quality, 5 violations of the maxim of relevance, and 3 violations of the maxim of manner. These violations generated implicatures that functioned as communication strategies to convey intended meanings indirectly, such as providing additional information, persuading and attracting buyers, maintaining prices, and expressing refusal. Therefore, maxim violations in buying and selling interactions do not merely indicate communication failure but can serve as pragmatic strategies to achieve communicative goals according to the context of interaction.